Novel insights into activated carbon derived from municipal solid waste for CO2 uptake: synthesis, adsorption isotherms and scale-up - Karimi, Mohsen (2020)
Recently, developing bio-based carbon materials due to the surface chemistry and a large spectrum of pore structures have received much attention. In the present work, a series of activated carbon (AC) adsorbents were synthesized from the compost derived by the mechanical/biological treatment of municipal solid wastes and evaluated regarding their CO2uptake. The AC samples were characterized by sulfuric acid and calcination by N2at 400 and 800 °C. Then, the CO2uptake capacities were evaluated by dynamic breakthrough experiments in a temperature range of 40-100 °C and pressures up to 3 bar. The presented data were properly described by Langmuir model and it was revealed that the CMSW-S-800 sample, treated with sulfuric acid and activated at 800 °C, has the highest CO2uptake capacity with an amount adsorbed around 2.6 mol/kg at 40 °C. In the next step, a mathematical model has been developed to match the experimental dynamic breakthrough data and design a pressure swing adsorption (PSA) cyclic process to evaluate the capacity and potential of the best AC sample for CO2adsorption. The results arising from this work showed a possible route for the application of the compost as a source of activated carbon for the sorption of greenhouse gases.